Leber's hereditary optic atrophy: further evidence for a defect of cyanide metabolism?. Issue 4 (April 1989) - Berninger, T A; von Meyer, L; Siess, E; Schon, O; Goebel, F D
Abstract : We studied one patient with Leber's optic atrophy (LOA) in the acute stage and 12 at the chronic stage of the disease, and measured the activity of rhodanese in white blood cells and the level of cyanide in whole blood. In the patient with acute disease the blood cyanide level was significantly increased at first. Treatment of this patient with cyanide antagonists reduced his cyanide level, but this was not accompanied by improvement in visual function. Rhodanese activity was normal in all patients, as were the blood cyanide levels in each of the 12 patients at the chronic stage of the disease. These findings suggest a temporary disturbance of cyanide metabolism during the acute phase of the disease in this family. The abnormal metabolic mechanism was not identified.